miR160 and miR166/165 Contribute to the LEC2-Mediated Auxin Response Involved in the Somatic Embryogenesis Induction in Arabidopsis - Wójcik, Anna M.; Nodine, Michael D.; Gaj, Małgorzata D. (Frontiers in Plant Science, 2017)
MicroRNAs are non-coding small RNA molecules that are involved in the post-transcriptional regulation of the genes that control various developmental processes in plants, including zygotic embryogenesis (ZE). miRNAs are also believed to regulate somatic embryogenesis (SE), a counterpart of the ZE that is induced in vitro in plant somatic cells. However, the roles of specific miRNAs in the regulation of the genes involved in SE, in particular those encoding transcription factors (TFs) with an essential function during SE including LEAFY COTYLEDON2 (LEC2), remain mostly unknown. The aim of the study was to reveal the function of miR165/166 and miR160 in the LEC2-controlled pathway of SE that is induced in in vitro cultured Arabidopsis explants.In ZE, miR165/166 controls the PHABULOSA/PHAVOLUTA (PHB/PHV) genes, which are the positive regulators of LEC2, while miR160 targets the AUXIN RESPONSE FACTORS (ARF10, ARF16, ARF17) that control the auxin signaling pathway, which plays key role in LEC2-mediated SE. We found that a deregulated expression/function of miR165/166 and miR160 resulted in a significant accumulation of auxin in the cultured explants and the spontaneous formation of somatic embryos. Our results show that miR165/166 might contribute to SE induction via targeting PHB, a positive regulator of LEC2 that controls embryogenic induction via activation of auxin biosynthesis pathway (Wójcikowska et al., 2013). Similar to miR165/166, miR160 was indicated to control SE induction through auxin-related pathways and the negative impact of miR160 on ARF10/ARF16/ARF17 was shown in an embryogenic culture. Altogether, the results suggest that the miR165/166- and miR160-node contribute to the LEC2-mediated auxin-related pathway of embryogenic transition that is induced in the somatic cells of Arabidopsis. A model summarizing the suggested regulatory interactions between the miR165/166-PHB and miR160-ARF10/ARF16/ARF17 nodes that control SE induction in Arabidopsis was proposed.